A study of compliance of breast Self-Examination among women of rural Maharashtra - Rashmi Gode; Chetna Maliye; A M Mehendale; B S Garg (Wolters Kluwer Medknow Publications, 2017)
Introduction: According to GLOBOCAN 2012, breast cancer is the second most prevalent cancer in world and the most frequent among women. In India, around 80,000 cases are estimated to occur annually. Survival from breast cancer depends on two main factors, early detection and optimal treatment. There are virtually no population-based breast cancer screening programs in developing countries. This community based study was carried out for creating awareness about Breast Self-Examination (BSE), the easiest method for early diagnosis and to assess the impact of interventional measures on acceptance of BSE. Objectives: To assess the awareness about breast cancer and BSE among 20 - 49 years women and to create awareness about breast cancer and BSE among 20 - 49 years women. Methods: It was an interventional study, conducted in the field practice area of a Medical College. Total of 310 women were assessed on Self-administered questionnaire filled by women in pre and post intervention for awareness of Breast cancer and BSE. Results: 3% women were aware of BSE at baseline which increased to 89.68% at end line. (p=0.001, p<0.05). There was statistically significant difference in attitude towards BSE (p=0.0001, p<0.05) at end-line and 92.90% women started performing BSE on regular basis. Conclusion: From selective review on practice and effectiveness of BSE, only 0% to 52% of women practice Breast Self-Examination on regular basis and there is no evidence of performing the procedure correctly. It is evident that BSE functions as an effective preventive health action.